2017
DOI: 10.1007/s40501-017-0100-6
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Treatment Options for Major Depressive Disorder in Older Adults

Abstract: Opinion Statement Late-life depression (LLD) is a public health concern with deleterious effects on overall health, cognition, quality of life, and mortality. Although LLD is relatively common, it is not a normal part of aging and is often under-recognized in older adults. However, psychotherapy is an effective treatment for LLD that aligns with many patients’ preferences and can improve health and functioning. This review synthesized the current literature on evidence-based psychotherapies for the treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 76 publications
0
20
0
Order By: Relevance
“…Care staff working in mental health facilities had significantly higher self-efficacy in end-of-life communication compared to care staff working in facilities for older people. This may be due to the experience of mental health staff with psychosocial interventions [42, 43]. Care staff in mental healthcare are also often trained in and accustomed to discussing complex and sensitive topics such as a wish to die [14].…”
Section: Discussionmentioning
confidence: 99%
“…Care staff working in mental health facilities had significantly higher self-efficacy in end-of-life communication compared to care staff working in facilities for older people. This may be due to the experience of mental health staff with psychosocial interventions [42, 43]. Care staff in mental healthcare are also often trained in and accustomed to discussing complex and sensitive topics such as a wish to die [14].…”
Section: Discussionmentioning
confidence: 99%
“…2, 3 Recent reviews illustrate a variety of aerobic, anaerobic and combined exercise interventions for patients with psychosis including running, walking, team sports, weight lifting, and yoga. 35 Indeed, there have been exciting developments in exercise interventions in schizophrenia populations, and findings suggest that exercise may improve symptom, cognitive, cardiovascular, social and role functioning, and neurobiological domains; potentially facilitating greater quality of life and well-being for people with debilitating mental illnesses. 3, 611 Given the demonstrated benefits of exercise interventions in those with a formal psychotic disorder, the current study aims to test the feasibility of an aerobic exercise intervention prior to the onset of the illness.…”
Section: Introductionmentioning
confidence: 99%
“…Interventions for older adults with chronic illness have found that while antidepressant pharmacotherapy is effective to address depressive symptoms, most older adults prefer psychotherapeutic or psychoeducational interventions over medication. 1012 While there is a growing psychotherapy evidence base for older adults broadly, 13,14 we identified only two studies focusing on older patients with cancer. In one, a multidisciplinary team offered treatment to older adults with cancer, including physical therapy, cognitive behavioral training, symptom education, spiritual guidance, and a 200-page manual.…”
Section: Introductionmentioning
confidence: 99%
“…Interventions for older adults with chronic illness have found that while antidepressant pharmacotherapy is effective to address depressive symptoms, most older adults prefer psychotherapeutic or psychoeducational interventions over medication. [10][11][12] While there is a growing psychotherapy evidence base for older adults broadly, 13,14 we identified only two studies focusing on older patients with cancer.…”
mentioning
confidence: 99%